Hydrogen from waste: technical feasibility of thermal waste treatement for decarbonization of economy - Ong, Joel Wen Jun (Nanyang Technological University, 2023)
To reach the 2015 Paris Agreement to limit global warming to between 1.5oC and 2.0oC of pre-industrial levels, the world will need to reduce carbon emissions. Currently, the largest carbon emissions source is from the energy sector, accounting for 34% of global emissions. Hence, it is imperative to decarbonize the energy sector to reach the Paris Agreement goals. Alternative low carbon energy sources such as hydrogen would be needed to decarbonize the energy sector. Additionally, the world is generating increasing amounts of waste that take up valuable land space as landfills and pollutes environment. To tackle these 2 issues, this project explored the possibility of generating hydrogen from waste, using wastewater sludge, refused derived fuel (RDF), biomass, and marine litter. A pyrolysis-thermolysis process was employed to produce hydrogen and solid carbon by-product that could store carbon. For this process to be viable, this project investigated technical and economic aspects of hydrogen production, including technical feasibility in terms of material recovery, product characteristics, energy requirements and potential value recovery. For the experiment, feedstock was fed into the pyrolysis reactor at a rate of 15g/min at 600oC. After a stabilisation period of 20 – 30 minutes, the pyrolysis gas was collected and the pyrolysis reactor was connected to the thermolysis reactor, operating at 1300oC. The product gas from the thermolysis reactor was collected for a period of 30 minutes. Both pyrolysis and product gases were analysed while pyrolysis oil and solid carbon were collected after the pyrolysis and thermolysis process, respectively. From the experiments, it was found that the pyrolysis and thermolysis are technically feasible, producing hydrogen purity of 56.1vol.% without CO2 sorbent and 67.1 vol.% with CO2 sorbent. Thermolysis increased the hydrogen purity from the pyrolysis gas by an average of 270% and 132% for experiments without CO2 sorbent and experiments with CO2 sorbent, respectively. However, the mass yield of hydrogen was relatively low (0.7 – 1.9 wt.%). The solid carbon produce contained over 90 wt.% carbon. The pyrolysis oil produced was of varying quality. The repurposing of waste products helped make this process economically viable as economic analysis revealed that both the pyrolysis and thermolysis processes could yield better margins compared to incineration. Overall, this project affirmed the feasibility of producing hydrogen from waste to decarbonize the economy. This study concluded that among the four feedstocks, RDF usage was preferable because of the following: (i) The hydrogen purity in product gases was the highest for experiments with and without CO2 sorbent, (ii) The hydrogen yield as a percentage of mass was the highest for experiments with and without CO2 sorbent, and (iii) Economically, RDF has a significant net gross margin per tonne of feedstock with and without CO2 sorbent.